2017
DOI: 10.1002/met.1647
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of regional drought events in southern China

Abstract: In this paper, an objective identification technique for regional extreme events (OITREE) is used to identify regional drought events (RDEs) in southern China based on the daily precipitation dataset of 342 stations from 1961 to 2012. Generally RDEs in southern China occur over an entire year, with high frequencies from January to April and peak frequencies in February and March. The spatial distributions of frequency and intensity of RDEs are consistent, with high frequencies of more than 60 and the annual av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In western NWC, the soil relative humidity and precipitation were also observed to have a significant increasing trend (Tan and Shao, ; Zhang et al, ), which may result in an increasing SPEI. Nevertheless, stations that experienced decreasing trends were mainly found in western SC and central NC (Figure a), and many previous studies have proved the same results (Zhang et al, ; ; Wang and Yan, ). The precipitation in central and southern NC has continued to decrease significantly due to the Pacific decadal oscillation (PDO) changes from a cold to a warm phase in the late 1970s.…”
Section: Resultssupporting
confidence: 74%
“…In western NWC, the soil relative humidity and precipitation were also observed to have a significant increasing trend (Tan and Shao, ; Zhang et al, ), which may result in an increasing SPEI. Nevertheless, stations that experienced decreasing trends were mainly found in western SC and central NC (Figure a), and many previous studies have proved the same results (Zhang et al, ; ; Wang and Yan, ). The precipitation in central and southern NC has continued to decrease significantly due to the Pacific decadal oscillation (PDO) changes from a cold to a warm phase in the late 1970s.…”
Section: Resultssupporting
confidence: 74%
“…Some studies have shown that it is necessary to represent the oceanic frontal zones and their influence on the storm track and atmospheric circulation with high‐resolution data and models (Nonaka et al, ; Taguchi et al, ; Wang & Yan, ; Woollings et al, ). High‐resolution SST can well represent the narrow sharp oceanic frontal zones with large amplitude (Wang & Yan, ), which contribute positively to the large surface baroclinicity by baroclinic adjustment via sensible heat flux, and accordingly, the storm tracks are enhanced and the westerly jet is increased as well (Doyle & Warner, ; Masunaga et al, ; Minobe et al, ; Nakamura et al, ; Small et al, ; Taguchi et al, ; Woollings et al, ). On the other hand, high‐resolution SST may also introduce many more mesoscale oceanic eddies with their diameter larger than 200 km in the North Pacific (Petersen et al, ), and the Kuroshio Extension (KOE) is one of the most active regions of oceanic eddies with a minimum lifespan of 4 weeks (Cheng et al, ; Petersen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the identified and recorded events are consistent, and the latter shows a shorter duration and smaller area than the former. This discrepancy might be because a drought event was not observed and recorded until it causes adverse social impacts after its emergence (Wang and Yan 2017).…”
Section: Discussionmentioning
confidence: 99%